Why heaven doesn't make earth absolutely meaningless, just relatively - Mawson, T (Cambridge University Press, 2020)
In this article, I seek charitably to develop an argument suggested by Thaddeus Metz. This is an argument against the view that it is consistent to hold that, while our lives may have some meaningfulness even if there is no heavenly afterlife awaiting us, if there is such an afterlife, they are even more meaningful, because heaven adds a potential infinity of meaningfulness. Having developed this argument on Metz's behalf, I criticize it. I conclude that – while throwing out a number of interesting ideas and possibilities along the way – no argument along Metz's lines can finally reach the conclusion aimed for.